2007
DOI: 10.1007/s00421-007-0610-9
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of bloodflux measurements from the upper trapezius muscle during muscle contractions

Abstract: The aim of this study was to assess the blood flux responses to isometric contractions and recovery. We also wanted to assess the variations in Laser Doppler blood fluxes (LDF) within the upper trapezius muscles, the concordance between the left and right sides and the reliability of blood-flux measurements between contractions and over measurement days. Ten subjects, mean age 25 years (21-35 years), performed two isometric shoulder abduction contractions at 10% of maximal voluntary contraction torque (MVC), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, shoulder and neck pain occur commonly during work involving very low levels of muscle activity. Also the low level contraction like the work task increased the trapezius muscle blood flux [3,9]. Furthermore, subjects with neck pain did not differ from the healthy subjects in the EMG levels of the trapezius muscles during the work task [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, shoulder and neck pain occur commonly during work involving very low levels of muscle activity. Also the low level contraction like the work task increased the trapezius muscle blood flux [3,9]. Furthermore, subjects with neck pain did not differ from the healthy subjects in the EMG levels of the trapezius muscles during the work task [3].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, activation of skeletal muscle fibers by somatic nerves leads to vasodilation. A previous study showed that low-level static contraction did increase trapezius muscle blood flux [9]. A lot of the results in an association between muscle activity and pain are not consistent.…”
Section: Introductionmentioning
confidence: 99%
“…In the inactive trapezius the baseline level was approached. Røe et al (2008) have reported reliable intramuscular LDF blood flux measurements during resting conditions and low-level contractions, and LDF signals due to artifacts were eliminated (Fig. The LDF probes measure the microcirculation in 1 mm 3 hemispheres which may not be representative for the muscle as a whole.…”
Section: Blood Fluxmentioning
confidence: 99%
“…Res. 20, 2009; 140-144. doi: 10.1111/j.1600-0501.2008.01631.x muscular, gingival, pulpal, and oral mucosal tissues (Donos et al 2005;Kocabalkan & Turgut 2005;Mavropoulos et al 2007;Retzepi et al 2007;Seike et al 2007;von Arx et al 2007;Emshoff et al 2008;Rajan et al 2008;Re et al 2008;Singh et al 2008). Several animal and a few clinical human studies assessing bone vascularity by LDF have also been carried out (Beaulé et al 2006(Beaulé et al , 2007Murnaghan et al 2006).…”
Section: Date: Accepted 20 June 2008mentioning
confidence: 99%